Looking for answers? Westonci.ca is your go-to Q&A platform, offering quick, trustworthy responses from a community of experts. Discover precise answers to your questions from a wide range of experts on our user-friendly Q&A platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
Sure, let's solve the given equation step by step:
Given equation:
[tex]\[ 3(2y + 4) = 4\left(2y - \frac{1}{2}\right) \][/tex]
1. Distribute the constants on both sides:
On the left side:
[tex]\[ 3 \cdot (2y) + 3 \cdot 4 = 6y + 12 \][/tex]
On the right side:
[tex]\[ 4 \cdot (2y) + 4 \cdot \left(-\frac{1}{2}\right) = 8y - 2 \][/tex]
Therefore, we have:
[tex]\[ 6y + 12 = 8y - 2 \][/tex]
2. Combine like terms:
First, isolate the terms with [tex]\( y \)[/tex] on one side and the constant terms on the other side. To do that, we can subtract [tex]\( 6y \)[/tex] from both sides:
[tex]\[ 6y + 12 - 6y = 8y - 2 - 6y \][/tex]
[tex]\[ 12 = 2y - 2 \][/tex]
3. Isolate the variable [tex]\( y \)[/tex]:
Add 2 to both sides to remove the constant term from the right side:
[tex]\[ 12 + 2 = 2y - 2 + 2 \][/tex]
[tex]\[ 14 = 2y \][/tex]
4. Solve for [tex]\( y \)[/tex]:
Divide both sides by 2:
[tex]\[ \frac{14}{2} = \frac{2y}{2} \][/tex]
[tex]\[ y = 7 \][/tex]
Therefore, the solution is [tex]\( y = 7 \)[/tex].
Given equation:
[tex]\[ 3(2y + 4) = 4\left(2y - \frac{1}{2}\right) \][/tex]
1. Distribute the constants on both sides:
On the left side:
[tex]\[ 3 \cdot (2y) + 3 \cdot 4 = 6y + 12 \][/tex]
On the right side:
[tex]\[ 4 \cdot (2y) + 4 \cdot \left(-\frac{1}{2}\right) = 8y - 2 \][/tex]
Therefore, we have:
[tex]\[ 6y + 12 = 8y - 2 \][/tex]
2. Combine like terms:
First, isolate the terms with [tex]\( y \)[/tex] on one side and the constant terms on the other side. To do that, we can subtract [tex]\( 6y \)[/tex] from both sides:
[tex]\[ 6y + 12 - 6y = 8y - 2 - 6y \][/tex]
[tex]\[ 12 = 2y - 2 \][/tex]
3. Isolate the variable [tex]\( y \)[/tex]:
Add 2 to both sides to remove the constant term from the right side:
[tex]\[ 12 + 2 = 2y - 2 + 2 \][/tex]
[tex]\[ 14 = 2y \][/tex]
4. Solve for [tex]\( y \)[/tex]:
Divide both sides by 2:
[tex]\[ \frac{14}{2} = \frac{2y}{2} \][/tex]
[tex]\[ y = 7 \][/tex]
Therefore, the solution is [tex]\( y = 7 \)[/tex].
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.